Acidente de moto em Picos: uma análise de causalidades sociais inerentes aos acidentes de trânsito envolvendo motocicletas - Melo, Heleonardo Dantas de (2017)
In the paper that follows, we look at transport accidents, focusing on those that happened involving motorcycles, in the city of Picos-PI, mainly in the time period for the years 2013, 2014 and 2015. We tried to delineate possible relationships between the Cultural arrays of individuals as a meaning-generating structure [in the Weberian understanding of meaning] - for actions in traffic. The search of the research was to understand if these actions, thus oriented, would be possible to generate behaviors that amplified the possibilities of an accident to occur. The methodological framework used is a starting point for the construction and application of a victimization survey on traffic accidents in Picos. We thus aimed to understand the degree of the problem "traffic accidents" focusing on those that occurred with motorcycles. In order to search for a sociological interpretation of the focused problem, we follow the path of the theoretical apparatus of the sociologist Bernar Lahire. This author has provided us with the basic structure for the construction of the sociological portraits of some of the fatal victims of the phenomena in question, it also served as the basis for a sociological portrait of the way the accident occurred. We also use the Weberian analytical framework of ideal types to follow the social relations existing in the transits and to design it as an environment of behavior, following to this interpretive "focus" Goffman's notes. Bourdieu's habitus theory is critically summed up to this analytical framework. In this way, we design our methodological tool.